Impact of winding on nanoimprinted surfaces in roll‐to‐roll nanoimprint lithography. Issue 8 (10th June 2022) - Jambhapuram, Manogna; Good, James K.; Azoug, Aurélie
Abstract: Roll‐to‐Roll manufacturing aims at scaling ultraviolet‐ and thermally cured nanoimprint lithography (UV‐NIL, T‐NIL) to commercial production speeds and volumes. Winding is the only convenient way of storing large quantities of nanoimprinted webs as they await unwinding in sequential R2R processes with distinct transport speeds. At production speeds, the imprinted resin is still chemically evolving when the imprinted web enters the winder, through a phenomenon called dark curing. The viscoelastic resin at various curing stages deforms under the contact pressure due to winding. This study is concerned with the impact of the contact pressure on the imprinted peak heights and potentially the functionality of the nanoimprinted surface. We develop a multiscale numerical model of the winding of the imprinted web. First the evolving properties of the resin through time are characterized, combining the effect of dark curing and viscoelasticity on the time‐dependent properties. Second, a finite element model of the imprinted web uses the resin mechanical properties to determine the effective properties of the imprinted web. Finally, the winding model determines the pressure and resulting strain of the imprints in the wound roll. The surface creep is quantified. This prediction will establish how and how long the imprinted materials should be wound. Abstract :